Oxidative Stress Protection by Exogenous Delivery of rhHsp70 Chaperone to the Retinal Pigment Epithelium (RPE), a Possible Therapeutic Strategy Against RPE Degeneration - Subrizi, Astrid; Toropainen, Elisa; Ramsay, Eva; Airaksinen, Anu J.; Kaarniranta, Kai; Urtti, Arto (Pharmaceutical research, 2015)
Purpose To measure the cytoprotective effects of rhHsp70 against oxidative stress and study its cellular uptake, intracellular and intraocular distribution in the retinal pigment epithelium. Methods Human retinal pigment epithelial cells (ARPE-19) were pre-treated with rhHsp70 for 24 h, 48 h, and 72 h before being exposed to 1.25 mM hydrogen peroxide. Non-treated cells served as control. We analysed interleukin 6 secretion, cell viability, and cytolysis. Uptake and intracellular distribution of fluorescently labelled rhHsp70 were investigated with flow cytometry and confocal microscopy, respectively. Ocular distribution of radioactively labelled rhHsp70 was followed ex vivo in porcine eyes by micro SPECT/CT. Results After exposure to hydrogen peroxide, IL-6 secretion decreased by 35–39% when ARPE-19 cells were pre-treated with rhHsp70. Cell viability increased by 17–32%, and cell lysis, measured by the release of lactate dehydrogenase, decreased by 6-43%. ARPE-19 cells endocytosed rhHsp70 added to the culture medium and the protein was localized in late endosomes and lysosomes. Following intravitreal injection into isolated porcine eyes, we found 20% rhHsp70 in the RPE. Conclusions Recombinant hHsp70 protein offers protection against oxidative stress. RPE cells take up the exogenously delivered rhHsp70 and localize it in late endosomes and lysosomes. This work provides the basis for a therapeutic strategy to target aggregate-associated neurodegeneration in AMD.